Achieving optimal SERS through enhanced experimental design. (16th December 2015) - Fisk, Heidi; Westley, Chloe; Turner, Nicholas J.; Goodacre, Royston
Abstract : One of the current limitations surrounding surface‐enhanced Raman scattering (SERS) is the perceived lack of reproducibility. SERS is indeed challenging, and for analyte detection, it is vital that the analyte interacts with the metal surface. However, as this is analyte dependent, there is not a single set of SERS conditions that are universal. This means that experimental optimisation for optimum SERS response is vital. Most researchers optimise one factor at a time, where a single parameter is altered first before going onto optimise the next. This is a very inefficient way of searching the experimental landscape. In this review, we explore the use of more powerful multivariate approaches to SERS experimental optimisation based on design of experiments and evolutionary computational methods. We particularly focus on colloidal‐based SERS rather than thin film preparations as a result of their popularity. © 2015 The Authors. Journal of Raman Spectroscopy published by John Wiley & Sons, Ltd. Abstract : A common limitation of SERS, restricting its commercial applications, is the lack of reproducibility. More often than not, researchers employ the 'one factor at a time' optimisation approach, resulting in an inefficient way of searching the experimental landscape. This review explores the use of more powerful multivariate approaches to experimental optimisation based on design of experiments and evolutionary computational methods (genetic algorithm).